PENGEMBANGAN MODUL BIOLOGI BERMUATAN PENDIDIKAN KARAKTER PADA MATERI SISTEM REPRODUKSI MANUSIA KELAS XI SMA - Afriadi, Roni; Lufri, Lufri; Razak, Abdul (Kolaboratif, 2013)
The research aims at producing module containing caracter education which are valid, practical and effective. The research was development research by using 4D models, namely 1) define (specify material) 2) design 3) develop 4) dessiminate (spread). The research only conducted until develop stage due to the limitation of time, fund and power. Subject trial to develop the module was XI grade student at SMAN 2 Padang. The reason for choosing the subject was the pilot schools suit the researcher's need and the school didn't use the module yet. Result module validity development which achieved 78,70% meaning that the module was valid to be used. Average module practicalities that achieved 87%Â meant that the module was practical. Average student's practicalities achievement were 86,76% and also considered that it was practical to be used in learning process. Averages tudent's activity achieved 74,4% from five categories observed and it meant that students were active in learning process. Cognitive assesments of test result showed that there were 92% students can solve the problems. Result product module character building education in human reproductive system in XI grade senior high school valid to be used, practical, effective.